Less-Invasive Approach to Early-Onset Scoliosis-Surgical Technique for Magnetically Controlled Growing Rod (MCGR) Based on Treatment of 2-Year-Old Child with Severe Scoliosis - Pawel Grabala; Ilkka J. Helenius; Kelly Chamberlin; Michael Galgano (MDPI AG, 2023)
Background: Spinal deformities in children can be caused by various etiologies, such as congenital, syndromic, neuromuscular, or idiopathic. Early-onset scoliosis (EOS) is diagnosed before the age of ten years, and when the curvature continues to progress and exceeds a Cobb angle of 60-65 degrees, surgical treatment should be considered. Initial minimally invasive surgery and the implantation of magnetically controlled growing rods (MCGRs) allows for the noninvasive distraction of the spine, growing, and avoids multiple operations associated with the classic distractions of standard growing rods. Case presentation: A 2-year-old girl was admitted to our clinic with rapidly progressive thoracic scoliosis. The major curve of the thoracic spine Cobb angle was 122° at 30 months. No congenital deformities were detected. The surgical technique was the less-invasive percutaneous and subfascial implantation of MCGRs, without long incisions on the back and the non-invasive ambulatory lengthening of her spine over the next 4 years. Conclusions: MCGR is a safe procedure for EOS patients. It is extremely effective at correcting spinal deformity; controlling the growth and curvature of the spine as the child develops during growth; reducing the number of hospitalizations and anesthesia; and minimizing the physical and mental burden of young patients, parents, and their families.